English learning autonomy among vocational college students in China: based on the three-aspect model - Zhang, Jing; Osman, Siti Zuraidah Md (Institute of Advanced Engineering and Science, 2024)
Based on the three-aspect model of learner autonomy, this study examines levels of English learning autonomy and potential correlation factors, such as gender, admission sources, and field of majors, in a newly-built vocational college in China. The study employs a random sampling survey method and surveyed 280 students from a Chinese public vocational college. After data analysis with quantitative methods, this study found that 48.6% respondents presented high-level English learning autonomy, followed by 43.6% and 7.9% students with moderate-level and low-level English learning autonomy respectively. Additionally, vocational college students developed moderate self-management learning ability (mean=3.57) and autonomous behaviors (mean=3.48) remained to be improved even though vocational college developed high level of autonomous psychology (mean=3.81). With regard to influential factors of English learning autonomy among vocational college students, admission sources can be considered as the most important factor to determine different levels of English learning autonomy, but no significant correlation exists between English learning autonomy and gender or field of majors. In response to such situation, suggestions are put forward to enhance English learning autonomy from the perspective of learning agenda, learning strategies, selfassessment, reflection, and digital learning materials.